1998
DOI: 10.1094/mpmi.1998.11.11.1119
|View full text |Cite
|
Sign up to set email alerts
|

Production of Acyl-Homoserine Lactone Quorum-Sensing Signals by Gram-Negative Plant-Associated Bacteria

Abstract: Many gram-negative bacteria regulate expression of specialized gene sets in response to population density. This regulatory mechanism, called autoinduction or quorum-sensing, is based on the production by the bacteria of a small, diffusible signal molecule called the autoinducer. In the most well-studied systems the autoinducers are N-acylated derivatives of L-homoserine lactone (acyl-HSL). Signal specificity is conferred by the length, and the nature of the substitution at C-3, of the acyl side-chain. We eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
465
1
11

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 570 publications
(489 citation statements)
references
References 45 publications
8
465
1
11
Order By: Relevance
“…Thus, b-galactosidase enzyme cleaves the X-gal reagent added in colorimetric bioassays, producing a blue-green indigo derivative. 6 This interesting biological test reveals that there is a cascade of biochemical reactions induced by the interaction of 1 with the mutated A. tumefaciens cells, as also observed for Ti oncogenic plasmid transfer in the crown gall disease in wild type strains. 5,6 The interaction of 1 with TraR receptor protein was solved based on X-ray diffraction of a crystallized complex dimer.…”
Section: Introductionmentioning
confidence: 66%
See 3 more Smart Citations
“…Thus, b-galactosidase enzyme cleaves the X-gal reagent added in colorimetric bioassays, producing a blue-green indigo derivative. 6 This interesting biological test reveals that there is a cascade of biochemical reactions induced by the interaction of 1 with the mutated A. tumefaciens cells, as also observed for Ti oncogenic plasmid transfer in the crown gall disease in wild type strains. 5,6 The interaction of 1 with TraR receptor protein was solved based on X-ray diffraction of a crystallized complex dimer.…”
Section: Introductionmentioning
confidence: 66%
“…6 This interesting biological test reveals that there is a cascade of biochemical reactions induced by the interaction of 1 with the mutated A. tumefaciens cells, as also observed for Ti oncogenic plasmid transfer in the crown gall disease in wild type strains. 5,6 The interaction of 1 with TraR receptor protein was solved based on X-ray diffraction of a crystallized complex dimer. The study revealed the main anchoring sites of 1 with different aminoacid residues and the protein structural changes induced by complexation that increases the complex affinity to specific DNA-binding sites.…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…Estas moléculas apresentam baixo peso molecular, são produzidas por diversas bactérias e apresentam a capacidade de atuar na comunicação celular bactéria-bactéria e bactéria-planta (CHA et al, 1998;GRAM et al, 1999) A formação de biofilme é determinada por uma seqüência de genes que podem induzir as células bacterianas a se aderirem a uma superfície e posteriormente estruturar um biofilme. Para X. fastidiosa, tem sido sugerido que o biofilme seja importante para obstrução dos vasos, fato este que poderia ser um importante fator de patogênese (MARQUES et al, 2002).…”
Section: Biofilmes Bacterianos E Comunicação Celular (Quorum Sensing)unclassified